Development of bioluminescent reporter Trypanosoma cruzi and bioassay for compound screening - Quiroga, Cristina; Incerti, Marcelo; Benitez, Diego; Manta, Eduardo; Medeiros, Andrea; Comini, Marcelo A. (Frontiers in Chemical Biology, 2024)
Trypanosoma cruzi is the etiologic agent of Chagas’ disease, a debilitating and mortal zoonotic illness that threatens the lives of several millions of people in the American continent. The acute phase is underdiagnosed and there is no curative treatment for the chronic stage. This unicellular pathogen colonizes cells from different tissues wherein it replicates and remains hidden from immune recognition. There is an urgent need to develop new chemotherapy, which requires robust screening bioassays against the amastigote, a proliferative and drug-resilient intracellular stage of the parasite. With this aim, here we present the generation and characterization of a bioluminescent reporter cell line of the highly infective strain Dm28c from T. cruzi. Constitutive and stable expression of the reporter gene (a red-shifted luciferase from Photinus pyralis) was achieved in the different developmental stages of the pathogen. The transgene did not affect parasite growth and differentiation. The bioluminescence signal displayed a linear correlation with the parasite number. A 96-well screening assay against the amastigote stage has been established and validated with a small compound library. The bioassay proved sensitive, robust, and amenable for high throughput applications. The reporter cell line may prove highly valuable to address different goals in the early phase of the drug discovery process against American trypanosomiasis.